Explaining the aggregate price level with Keynes's principle of effective demand - Jochen Hartwig (ETH Zurich, KOF Swiss Economic Institute, 2004)
The conventional wisdom about Keynes's Principle of Effective Demand is that it states something about quantities. It is widely held that the Principle determines the levels of output and employment in a world not governed by Say's Law. This paper argues that the Principle of Effective Demand goes beyond this to explain not only real activity levels but also the aggregate price level. A variant of the Post Keynesian D/Z-model is brought together with Marxian reproduction schemes to derive this result.
Keywords: B14; B22; E20; E31; 330; Effective demand; multiplier; Post Keynesianism; D/Z-model; reproduction schemes; Gesamtwirtschaftliche Nachfrage; Multiplikator; Preisniveau; Postkeynesianismus; Theorie